Photo- and thermally stimulated luminescence of polyminerals extracted from herbs and spices - Cruz Zaragoza, Epifanio (2012)
Ionizing radiation processing is a widely employed method for preservative treatment of foodstuffs. Usually it is possible to detect irradiated herbs and spices by resorting to luminescence techniques, in particular photo- and thermostimulated luminescence. For these techniques to be useful, it is necessary to characterize the response to radiation of each particular herb or spice. In this work, the thermoluminescence (TL) and photostimulated luminescence (PSL) properties of inorganic polymineral fractions extracted from commercial herbs and spices previously irradiated for disinfestation purposes have been analyzed. Samples of mint, cinnamon, chamomile, paprika, black pepper, coriander and Jamaica flower were irradiated from 50 to 400 Gy by using a beta source. The X-ray diffraction (XRD) analysis has shown that the mineral fractions consist mainly of quartz and feldspars. The PSL and TL response as a function of the absorbed dose, and their fading at room temperature have been determined. The TL glow curves have been deconvolved in order to obtain characteristic kinetics parameters in each case. The results of this work show that PSL and TL are reliable techniques for detection and analysis of irradiated foodstuffs.